Minimal main pancreatic duct dilatation in small branch duct intraductal papillary mucinous neoplasms associated with high-grade dysplasia or invasive carcinoma. Issue 3 (March 2021) - Amini, Neda; Rezaee, Neda; Habib, Joseph R.; Blair, Alex; Beckman, Ross M.; Manos, Lindsey; Cameron, John L.; Hruban, Ralph H.; Weiss, Matthew J.; Fishman, Elliot K.; Zaheer, Atif; Lafaro, Kelly J.; et al.
Abstract: Background: The aim of this study was to determine the incidence of high-grade dysplasia (HGD) or invasive carcinoma in patients with small branch duct intraductal papillary mucinous neoplasms (BD-IPMNs). Methods: 923 patients who underwent surgical resection for an IPMN were identified. Sendai-negative patients were identified as those without history of pancreatitis or jaundice, main pancreatic duct size (MPD) <5 mm, cyst size <3 cm, no mural nodules, negative cyst fluid cytology for adenocarcinoma, or serum carbohydrate antigen 19-9 (CA 19-9) <37 U/L. Results: BD-IPMN was identified in 388 (46.4%) patients and 89 (22.9%) were categorized as Sendai-negative. Overall, 68 (17.5%) of BD-IPMN had HGD and 62 (16.0%) had an associated invasive-carcinoma. Among the 89 Sendai-negative patients, 12 (13.5%) had IPMNs with HGD and only one patient (1.1%) had invasive-carcinoma. Of note, older age (OR 1.13, 95% CI 1.03–1.23; P = 0.008) and minimal dilation of MPD (OR 11.3, 95% CI 2.40–53.65; P = 0.002) were associated with high-risk disease in Sendai-negative patients after multivariable risk adjustment. Conclusion: The risk of harboring a high-risk disease remains low in small BD-IPMNs. However, Sendai-negative patients who are older than 65 years old and those with minimal dilation of MPD (3–5 mm) are at greater risk of high-risk lesions and should be given consideration to be included as a "worrisome feature" in a future guidelines update.